Real-Time Facial Motion Capture Using a Webcam - Kajan, Peter; Kamencay, Patrik; Hlubik, Jan; Hudec, Robert; Benco, Miroslav; Sykora, Peter (Communications - Scientific Letters of the University of Zilina, 2016)
In this paper, we create a software which would be able to combine marker and marker-less face tracking for the purpose of the creation of the accurate and real time running 3D facial animation inside the Cinema 4D. The aim is develop a powerful piece of the software that can provide facial motion capture and share the motion coordinates on the server in real time. The software solution includes tracking software which is written in C++ and provides real time face tracking. Tracking data are sent to the server in real time. Main benefit is that this solution can provide tracking data on the server for any third software. At least, the smooth run of the above mentioned real time tracking software requires simple color webcam with VGA resolution, running on 30 frames per second and a multi-core processor including at least two threads.
Keywords: facial motion capture; C; face tracking; 3D facial animation